Guachapelí vs Marabú and the Kinetic pyrolysis - Cantos Macías, Manuel Ángel; Quesada González, Omaida; Rodríguez Mcfarlanes, Rafael; Brito Soubanell, Angel Luis; Casanova Gómez, Abdel (Revista Cubana de Química, 2017)
The uses of forest residues or bushes, such as the Marabou, as a renewable resource of energy take economic and environmental importance. This work aims to characterize the Guachapelí (Ecuadorian) and Marabou (Cuban) woods chemically and energetically and study their kinetics of pyrolytic devolatilization. For this purpose, elemental, immediate analysis, and thermal analysis techniques such as Thermogravimetric Analysis, Differential Thermogravimetric and Differential Scanning Calorimetry were performed. The study showed that the chemical characteristics of the biomasses examined explain the high values of determined higher caloric power, and justify their sustainable thermal energy utilization. The kinetic analysis of the pyrolytic decomposition of these biomasses determined the kinetic models and activation energy for each step. Besides, the combination of the Coats (Integral) and Achar (Differential) equations contributes to counteract the limitations of the model-fitting Method with respect to the kinetic model. Keywords: wood residues, pyrolysis, kinetic, guachapelí, marabú.